Interacting Fat1 and Dchs Planar Cell Polarity Proteins Supported by Fjx1 Serve as Heterodimeric Intercellular Bridges Crucial to Support Spermatogenesis. - Bu, T.; Wang, L.; Wu, X.; Gao, S.; Yun, D.; Mao, B.; Li, L.; Sun, F.; Cheng, C.Y. (Advances in Experimental Medicine and Biology, 2025)
Studies of the planar cell polarity (PCP) protein complexes Fat1/Fjx1 and Dchs/Fjx1 that form heterotypic interacting bridges of Fat1-Dchs between adjacent cells to confer PCP, as noted in Drosophila, are also found in mammalian cells and tissues as orthologs, such as in Sertoli cells and condensed spermatids in the seminiferous epithelium of the testis. Recent studies have shown that these two interacting PCP protein complexes are also crucial regulators of microtubule and actin dynamics, modulating the polymerization of both microtubules and actin filaments in the testis. In this review, we provide a brief update and thought-provoking concept on the PCP core proteins and the associated downstream signaling pathways utilized by PCP proteins to confer PCP and regulation of the microtubule and actin cytoskeletons in the testis. However, we focus on recent data in the field on the Fat1/Fjx1 and Dchs/Fjx1 protein complexes, which are also heterotypic interacting protein complexes, and their functional role in modulating the microtubule and actin cytoskeletal organization. Based on these recent findings, we formulate a hypothetic model depicting the role of these two PCP protein complexes in modulating the timely "opening" and "closing" of the blood-testis barrier (BTB) formed by adjacent Sertoli cells near the base of the seminiferous epithelium. Additionally, these two PCP protein complexes also modulate cytoskeletal dynamics between Sertoli cells and condensed spermatids to support haploid spermatid transport across the seminiferous epithelium during their structural transformation through spermiogenesis, and their eventual release at spermiation during the epithelial cycle of spermatogenesis. This hypothetical model will provide a useful framework for designing functional experiments to understand the role of PCP proteins in supporting spermatogenesis.